Estimating Cloud and Rain Parameters from Doppler Radar Data - Bezvesilniy, O.O.; Peters, G.; Vavriv, D.M. (Радиофизика и радиоастрономия, 2003)
Real-time mapping of the parameters of precipitating water clouds and rain making use of a vertically-directed Doppler radar is an important problem. In this paper, an algorithm based on an independent estimation of the droplet effective diameter and concentration is suggested. This approach differs from the Marshall-Palmer retrieval procedure that is based on a single estimated parameter, the radar reflectivity factor. It is shown that the Marshall-Palmer approach can provide good estimates of the averaged parameters, however is not suitable for producing the high resolution time-height maps of the parameters. The two-parameter retrieval algorithm under discussion was tested using the data obtained with the 36 GHz polarimetric Doppler cloud radar MIRA-36. The results of the measurements and their processing are presented. The algorithm suggested has appeared to be applicable for real-time measurements with the vertically-directed Doppler radars.